2020
DOI: 10.1007/s41809-020-00061-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and linguistic predictors of bilingual single-word translation

Abstract: One of the advantages of being bilingual is the ability to translate from one language to the other. From language learners to professional interpreters, many different types of bilinguals engage in translation in their daily lives. How successful they are, however, depends on a wide range of factors. The current study aimed to identify the cognitive and linguistic variables that predict how quickly and accurately bilinguals are able to translate single words. Eighteen Chinese-English bilinguals listened to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(80 reference statements)
1
1
0
Order By: Relevance
“…The behavioral results revealed that participants’ interpreting performance was significantly correlated with their L2 proficiency and L2 exposure, but not with their age, age of L2 acquisition and L2 learning years. Our results on the one hand corroborated previous findings on the positive relation between L2 proficiency and interpreting/translation performance ( De Groot and Poot, 1997 ; Tzou et al, 2012 ; Mayor, 2015 ; Chen et al, 2020 ), on the other hand provided novel evidence on the association between interpreting performance and age, age of L2 acquisition and L2 learning years, which have never been reported before. Since interpreting performance was not influenced by age-related factors, we therefore regard interpreting as an activity that relies more on intensive training than on biological aptitude.…”
Section: Discussionsupporting
confidence: 90%
“…The behavioral results revealed that participants’ interpreting performance was significantly correlated with their L2 proficiency and L2 exposure, but not with their age, age of L2 acquisition and L2 learning years. Our results on the one hand corroborated previous findings on the positive relation between L2 proficiency and interpreting/translation performance ( De Groot and Poot, 1997 ; Tzou et al, 2012 ; Mayor, 2015 ; Chen et al, 2020 ), on the other hand provided novel evidence on the association between interpreting performance and age, age of L2 acquisition and L2 learning years, which have never been reported before. Since interpreting performance was not influenced by age-related factors, we therefore regard interpreting as an activity that relies more on intensive training than on biological aptitude.…”
Section: Discussionsupporting
confidence: 90%
“…They argue that lifelong practice of bilingualism can boost both the structural and functional properties of brain networks thereby enhancing cognitive functioning in old age. Chen et al (2020) examined performance in Chinese-English bilinguals on a translation production task. They collected both linguistic as well as cognitive control data.…”
mentioning
confidence: 99%